2015
DOI: 10.1136/annrheumdis-2015-207487
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and chondrocyte mineralisation act in tandem to promote experimental osteoarthritis

Abstract: BCP crystals and IL-6 form a positive feedback loop leading to OA. Targeting calcium-containing crystal formation and/or IL-6 are promising therapeutic strategies in OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 54 publications
7
91
1
2
Order By: Relevance
“…A similar difference was previously observed in the effects of IL-6 blockade upstream or downstream of its interaction with its gp130 receptor,18 so Stat3 may be activated independent of IL-6 by other gp130 cytokines. Notably, several studies have pointed to the role of oncostatin M (OSM) in synovial inflammation or osteophyte-like bone proliferation in mouse models 31 32.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A similar difference was previously observed in the effects of IL-6 blockade upstream or downstream of its interaction with its gp130 receptor,18 so Stat3 may be activated independent of IL-6 by other gp130 cytokines. Notably, several studies have pointed to the role of oncostatin M (OSM) in synovial inflammation or osteophyte-like bone proliferation in mouse models 31 32.…”
Section: Discussionsupporting
confidence: 76%
“…More recently, a positive feedback loop was identified between calcium-containing crystals and IL-6 leading to cartilage destruction 18. Despite these data, the mechanisms by which IL-6 elicits its effects in cartilage remain poorly known 19…”
Section: Introductionmentioning
confidence: 99%
“…OSM promotes matrix loss and disease progression 12 13. IL-6 suppresses chondrocyte proliferation,14 promotes mineralisation in AC,15 downregulates matrix proteins16 and increases expression of proteases 17 18. Moreover, blockade of IL-6 in mouse models of OA is chondroprotective 17 18.…”
Section: Introductionmentioning
confidence: 99%
“…Additional support for a role for inflammatory mediators in regulating ANK levels was recently supplied by Nasi et al They showed that IL-6, another important cytokine in crystal-induced arthritis, upregulated ANK, Annexin 5, and Pit-1 gene expression in murine cartilage explants [31]. …”
Section: Ank Regulationmentioning
confidence: 99%